2016
DOI: 10.1016/j.physletb.2015.12.011
|View full text |Cite|
|
Sign up to set email alerts
|

Updating neutrino magnetic moment constraints

Abstract: In this paper we provide an updated analysis of the neutrino magnetic moments (NMMs), discussing both the constraints on the magnitudes of the three transition moments Lambda_i as well as the role of the CP violating phases present both in the mixing matrix and in the NMM matrix. The scattering of solar neutrinos off electrons in Borexino provides the most stringent restrictions, due to its robust statistics and the low energies observed, below 1 MeV. Our new limit on the effective neutrino magnetic moment whi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 59 publications
2
55
0
Order By: Relevance
“…This range would imply a transition magnetic moment constraint of µ xy < ∼ 2.5 × 10 −10 µ B to 2σ. This is still roughly an order of magnitude above the recently found constraints on transition moments using sub-MeV Borexino data [16]. If we consider values of magnetic moments closer to the recent laboratory bounds, we find percent changes in D/H to be 0.021% , Y P to be 0.0021% , and N eff to be 0.068% for the case that all three transition moments are ∼ 7 × 10 −11 µ B .…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…This range would imply a transition magnetic moment constraint of µ xy < ∼ 2.5 × 10 −10 µ B to 2σ. This is still roughly an order of magnitude above the recently found constraints on transition moments using sub-MeV Borexino data [16]. If we consider values of magnetic moments closer to the recent laboratory bounds, we find percent changes in D/H to be 0.021% , Y P to be 0.0021% , and N eff to be 0.068% for the case that all three transition moments are ∼ 7 × 10 −11 µ B .…”
Section: Discussionsupporting
confidence: 57%
“…Such constraints were first found in [14] using available solar + reactor scattering data from experiments such as SNO, SuperK, ROVNO and MUNU. A recent analysis of sub-MeV Borexino scattering data [15] found constraints on the three Majorana transition moments in the mass basis to be µ ij ≤ [3.1 − 5.6] × 10 −11 µ B [16]. These new limits given by Borexino data are stronger than those found from MUNU and TEXONO data, and secondary only to constraints from GEMMA data which for Majorana moments are µ ij ≤ [2.9 − 5.0] × 10 −11 µ B [16].…”
Section: Introductionmentioning
confidence: 99%
“…Analyses of such limits in conjunction with different sets of data can be found in Refs. [17][18][19].…”
Section: Resultsmentioning
confidence: 99%
“…21, observed that the neutrino magnetic moment is bounded from above by the value μ ν < 2.9 × 10 −11 μ B and the bound obtained from Borexino, see Ref. 22, data gave μ ν ≤ 3.1 × 10 −11 μ B . Since a wide range of neutrino magnetic moments is possible up to the current laboratory upper limit beyond standard model, it is interesting to investigate the phenomenological consequences of the nonvanishing magnetic moment up to the current bounds, which may constrain the bound tighter than the direct measurements of the neutrino magnetic dipole moment.…”
mentioning
confidence: 84%